2010
DOI: 10.1109/tii.2010.2051813
|View full text |Cite
|
Sign up to set email alerts
|

Computing Optimal Schedules of Battery Usage in Embedded Systems

Abstract: The use of mobile devices is often limited by the battery lifetime. Some devices have the option to connect an extra battery, or to use smart battery-packs with multiple cells to extend the lifetime. In these cases, scheduling the batteries or battery cells over the load to exploit the recovery properties of the batteries helps to extend the overall systems lifetime. Straightforward scheduling schemes, like round robin or choosing the best battery available, already provide a big improvement compared to a sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 17 publications
(21 reference statements)
0
28
0
Order By: Relevance
“…In [5] it is shown that, according to the KiBaM model, in theory the best way to discharge the batteries in a multiple battery system is by using them in parallel. For a system with N identical batteries discharged with a continuous current I the lifetime is then given by:…”
Section: Maximum Possible Lifetime Gainmentioning
confidence: 99%
See 3 more Smart Citations
“…In [5] it is shown that, according to the KiBaM model, in theory the best way to discharge the batteries in a multiple battery system is by using them in parallel. For a system with N identical batteries discharged with a continuous current I the lifetime is then given by:…”
Section: Maximum Possible Lifetime Gainmentioning
confidence: 99%
“…The batteries that have been used in this computation are similar to those used in [5], i.e., c = 0.166 and k = 2.815·10 −4 s −1 . However, here the capacity is increased to a realistic value, C = 2400 As, instead of the much smaller capacity of 330 As used in [5]. This type of battery is used in the Itsy pocket computer, which was also simulated by Rakhmatov et al in [14,15].…”
Section: Maximum Possible Lifetime Gainmentioning
confidence: 99%
See 2 more Smart Citations
“…- • Chapters 5 and 6 are extensions of [40] and [36]. The analytical approach to the scheduling problem presented in Chapter 6 was worked on in collaboration with Alexandru Mereacre.…”
Section: Origin Of the Chaptersmentioning
confidence: 99%